2019
DOI: 10.1093/ijnp/pyz060
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Consolation Behaviors in Physically Stressed Mandarin Voles: Involvement of Oxytocin, Dopamine D2, and Serotonin 1A Receptors Within the Anterior Cingulate Cortex

Abstract: Background Consolation is a type of empathy-like behavior that has recently been observed in some socially living rodents. Despite the growing body of literature suggesting that stress affects empathy, the relationship between stress and consolation remains understudied at the preclinical level. Here, we examined the effects of chronic emotional stress or physical stress exposure on consolation and emotional behaviors by using the socially monogamous mandarin vole (Microtus mandarinus) in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…The lack of consolation in surgery mice is conceivable because these mice were sick and suffered from pain and distress. Consistent with this possibility, physically stressed Mandarin voles have reduced consolation toward their social defeated partners 8 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The lack of consolation in surgery mice is conceivable because these mice were sick and suffered from pain and distress. Consistent with this possibility, physically stressed Mandarin voles have reduced consolation toward their social defeated partners 8 .…”
Section: Discussionmentioning
confidence: 83%
“…Consistent with our findings, orexin has been found to regulate anxiety and adaptation to stress 37 , 38 . Orexin signaling may be involved in consolation of Mandarin voles toward socially defeated partners 8 , 39 Orexinergic modulation of PVT neurons is reported from lateral hypothalamic area 19 , 34 . Our findings imply a role of lateral hypothalamic area in the consolation and anxious behaviors of familiar observers.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that these two types of receptors exert opposite effects within the mPFC (Celada et al, 2013;Puig and Gulledge, 2011). In our previous study, we indicated that ACC administration of a 5HT1AR agonist (8-OH-DPAT) rescued the impaired consolation and sociability induced by social defeat (Li et al, 2020). To further examine which receptor mediates consolation-like behaviors within the ACC, we directly infused 8-OH-DPAT (200 nL/side; 1.5 mg/mL) or a 5-HT2AR antagonist (MDL 100907, 200 nL/side; 1 mg/mL) into the ACC along with chemogenetic inhibition of DR 5-HT neurons before conducting behavioral assays ( Figure 6A & B).…”
Section: Acc 5-ht Release Increased During Allogrooming Social Appromentioning
confidence: 87%
“…The digital videos were viewed and quantified using J Watcher software (http://www.jwatcher.ucla.edu/). According to previous studies (Burkett et al, 2016; Li et al, 2019), allogrooming is designated as behavioral indicators of consolation, which defined as head contact with the body or head of their partner, accompanied by a rhythmic head movement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation